Mutation breeding in agriculture - Till, Bradley J. (Henry Stewart Talks, 2013)
Mutation breeding in agriculture, Background on plant mutation breeding, Key principles and examples of mutation breeding, Reverse genetics for functional genomic and breeding, Considerations for vegetatively propagated crops, New technologies for mutation assisted breeding